1990
DOI: 10.1002/ddr.430210305
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and metabolic profile of Cl‐966: A potent, orally‐active inhibitor of GABA uptake

Abstract: A lipophilic derivative of the known GABA uptake inhibitor guvacine has been prepared. The synthesis of this compound, [1-[2-bis[4-(trifluoromethyl)]phenyl]-methoxy]ethylj-l,2,5,6-tetrahydro-3-pyridine carboxylic acid, monohydrochloride, Cl-966, is described. Studies were carried out to determine the metabolic profile of Cl-966 in rats. Two metabolites, one less polar and the other more polar than Cl-966, were identified and their structures assigned by spectroscopic methods and confirmed by comparison to synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In addition, nipecotic acid is itself a substrate for the GABA uptake carrier and can be re-released in a calciumdependent manner on further neuronal depolarization and thus act as a false transmitter (Larsson et al, 1983;Krogsgaard-Larsen et al, 1987). Yunger et al (1984), Braestrup et al (1987Braestrup et al ( , 1990, Bjorge et al (1990), Nielsen et al (1991), and Andersen et al (1993) described novel series of lipophilic GABA uptake inhibitors that show potent activity in vitro and in vivo. These compounds differ from nipecotic and similar cyclic amino acid GABA uptake inhibitors (Krogsgaard-Larsen and Johnston, 1975) in that they readily cross the BBB due to increased lipophilicity after substitution of a lipophilic anchor on the amino acid nitrogen atom.…”
Section: Overview Of Gaba Neurotransmissionmentioning
confidence: 99%
“…In addition, nipecotic acid is itself a substrate for the GABA uptake carrier and can be re-released in a calciumdependent manner on further neuronal depolarization and thus act as a false transmitter (Larsson et al, 1983;Krogsgaard-Larsen et al, 1987). Yunger et al (1984), Braestrup et al (1987Braestrup et al ( , 1990, Bjorge et al (1990), Nielsen et al (1991), and Andersen et al (1993) described novel series of lipophilic GABA uptake inhibitors that show potent activity in vitro and in vivo. These compounds differ from nipecotic and similar cyclic amino acid GABA uptake inhibitors (Krogsgaard-Larsen and Johnston, 1975) in that they readily cross the BBB due to increased lipophilicity after substitution of a lipophilic anchor on the amino acid nitrogen atom.…”
Section: Overview Of Gaba Neurotransmissionmentioning
confidence: 99%
“…(9)) [96]. Examples are SKF 89976A, SKF 100330A [97], tiagabine ((R)-N-[4,4-di(3-methyl-2-thienyl)-3-butenyl]-3-piperidinecarboxylic acid) [98], NC-711 [99] and CI-966 [100], which have a suitable lipophilicity to enter the central nervous system after oral administration, are potent inhibtors of GABA uptake, and proved protective against seizures in some animal models. In addition, SKF 89976A, tiagabine, NC-711, and CI-966 are highly selective for GAT-1 [101].…”
Section: Gaba Transportermentioning
confidence: 98%
“…LAT-1 is important because it transports several prescription drugs, such as the antiparkinsonian drug L-dopa and the anticonvulsant gabapentin, across the BBB, thereby enabling their pharmacologic effects [10,11]. This function at the BBB has made LAT-1 a target for drug delivery by modifying CNS-impermeable drugs such that they become LAT-1 substrates and have enhanced BBB penetration [12][13][14][15].…”
Section: Design Considerationmentioning
confidence: 99%
“…Nipecotic acid fails to cross the BBB owing to its polar and zwitterionic nature. The potential antiepileptic activity of nipecotic acid coupled with its synthetic versatility has led to the synthesis of a vast number of structurally diverse lipophilic derivatives with marked antiepileptic activity [6][7][8][9][10][11][12][13]. It has been found that substances crossing the BBB through many pathways (Transmembrane diffusion, Carrier mediated-transport and transcytosis).…”
Section: Introductionmentioning
confidence: 99%